Realized Volatility Forecasting for AI-Mining Sensor Data Using the Multi Layer Perceptron Method - Obed Christian Dimitrio; Didit Budi Nugroho; Hanna Arini Parhusip; Atyanta Nika Rukmasari (Journal of Science and Science Education, 2021)
This study aims to predict the Realized Volatility (RV) value from AI-Mining sensor data for the period 23 May to 6 June 2022 by using the Multi Layer Preceptron (MLP) method. MLP is the simplest method of artificial neural network. Based on the results obtained after doing MLP with the Python language on Google Colab, the predicted RV value for each data shows a movement in value that is almost similar to the original RV value. The Root Mean Squares Error (RMSE) value for each data prediction is relatively small, which indicates that the MLP method provide accurate prediction on the use of the AI-Mining sensor data to forecast RV.